Highly pathogenic Aeromonas hydrophila in swine - Duarte, EL (2019)
OBJECTIVE Autochthonous Iberian pig breeds have been growingly popular due to the increasing demand for locally and extensively produced animals. Due to their different production system, microbiological hazards significantly diverge from industrially reared animals. Within the frame of a broader study to characterize specific pathogens associated with Alentejano pig breed, Aeromonas hydrophila was isolated in pure culture from collected organs of septicemic piglets from two farms. These farms had no epidemiological link between them to our knowledge. As A. hydrophila is seldom the cause of septicemia in mammals, antimicrobial resistance profile and virulence factors were investigated for these two strains. MATERIALS/METHODS Aeromonas hydrophila were phylogenetic characterized using gyrB gene sequencing. Antimicrobial resistance profile and the production of extracellular lipases and proteases was evaluated. The presence of several genetic determinants of resistance and virulence were determined by PCR: aminoglycoside resistance associated genes (acetyltransferases-AAC-, phosphotransferases-APH- and nucletildiltranferases-ANT), genes encoding lipases and aerolysin-related toxins and type III secretion system. RESULTS Identification was confirmed by gyrB sequencing. A. hydrophila isolate from farm 1 was sensitive to gentamicin, oxytetracycline, neomycin, enrofloxacin, colistin sulfate, trimethoprim, ceftiofur and amoxicillin/ clavulanic acid. A. hydrophila from farm 2 was resistant to all antibiotics except enrofloxacin. This isolate harboured APH(6)-I and ANT(6)-I genes, but no AAC genes. Genes for all virulence factors tested were present in both isolates. Moreover, all strains displayed lipolytic and proteolytic activity under the conditions tested. CONCLUSION Although described in immunocompromised humans or as a secondary pathogen, Aeromonas hydrophila has been unfrequently reported as a cause of septicemia in mammals. The occurrence of several virulence determinants in these emergent pathogens, their multiple resistance profile, along with their ubiquitous nature in terrestrial and aquatic environments, is prone to rise a significant concern to animal health and veterinary microbiologists in the near future.